2020
DOI: 10.4103/apjon.apjon_45_19
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Stigma and Depression in Cancer Patients in A Middle-Income Country

Abstract: Objective:The aim of the current study are to determine the depression levels of adult oncology patients in the cancer treatment phase and identify both cancer-related stigma and the factors affecting their depression levels.Methods:In this correlational study, 303 adult patients who had been treated at a medical outpatient clinic were surveyed using the convenience sampling method. The “questionnaire for measuring attitudes toward cancer – patient version,” a sociodemographic characteristics questionnaire, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
0
18
0
3
Order By: Relevance
“…Depending on the cancer type and cultural characteristics, the prevalence of perceived stigmatization greatly varies, ranging from 13 to 80% ( Cho et al, 2013 ; Yılmaz et al, 2019 ). About 26% of Iranian patients with cancer are psychologically stressed out by stigma ( Hasan Shiri et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the cancer type and cultural characteristics, the prevalence of perceived stigmatization greatly varies, ranging from 13 to 80% ( Cho et al, 2013 ; Yılmaz et al, 2019 ). About 26% of Iranian patients with cancer are psychologically stressed out by stigma ( Hasan Shiri et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Khamidah, Indra, and Lita, (2019), also found that the majority of breast cancer patients have a negative stigma against their disease and feel that they will soon die. Research Yılmaz et al, (2019) also found that in Turkish society there is a belief that cancer is incurable, cancer is fatal, patients with cancer are disabled, cancer patients cannot return to work, and cancer sufferers are incompetent. According to the researchers' assumptions, the development of this kind of assumption among the community is due to the often late arrival of cancer patients to health care centers so that they are already in an advanced stage where treatment options are limited and their life expectancy decreases.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with mixed cancer types, negative attitudes toward cancer were associated with being older than 60-year-old, possessing higher education, earning low income and feeling socially excluded [ 90 ]. Some inconsistencies were, however, found in the association between educational level and stigma in the included studies amongst patients with mixed cancer types [ 64 , 90 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was found that within person, fluctuations in stigma were related to social and role functioning in patients with lung cancer, regardless of physical symptoms and were not carried over to the next day [ 65 ]. Evidence of positive correlation between stigma and anxiety [ 11 , 88 ], depression [ 11 , 23 , 90 , 93 ], higher self-perceived burden [ 88 ], symptom burden [ 93 , 43 ] and affective interferences [ 37 ] were also reported. Body image and social support were found to mediate the relationship between stigma and depression in cancer patients [ 23 , 43 ].…”
Section: Methodsmentioning
confidence: 99%